Analisis Politik Luar Negeri Indonesia-China di Era Presiden Joko Widodo: Benturan Kepentingan Ekonomi dan Kedaulatan? - Muhammad Tri Andika; Allya Nur Aisyah (Indonesian Perspective, 2017)
Under Joko Widodo presidency, relations between Indonesia and China has increased dramatically. It is mainly marked by set of effort to intensify economic cooperation between the two countries, both in the investment and trade sectors. However, at the same time the two countries also involve in the territorial disputes, particularly in the Natuna’s waters area. Against that background, do these two different dynamics affect each other? This paper argues that two distinct dynamics circling the Indonesia-China relationship have no significant influence each other. This is because Indonesia’s diplomacy with China in economic and sovereignty has different character and structure of interests. In the economic field, relations between Indonesia and China have been pursued on the principle of pragmatic cooperation in the effort to increase trade and investment relations. While in the Natuna’s issue the relationship between the two countries is based on the principle of strategic importance. This article also argues that China’s investment flows to Indonesia in some infrastructure financing, does not affect Indonesia’s firmness in maintaining Natuna’s sovereignty.Keywords: Indonesia, China, Natuna, Investment